Review of literature on disseminated tuberculosis with emphasis on the focused diagnostic workup - Fahmi Y Khan (Wolters Kluwer Medknow Publications, 2019)
Disseminated tuberculosis (TB) is a life-threatening disease resulting from the hematogenous spread of Mycobacterium tuberculosis. The diagnosis is challenging owing to its subtle nonspecific clinical presentation, which usually reflects the underlying organ involved. Besides, tools for confirmatory laboratory diagnosis are limited. Therefore, a high index of suspicion is required for early diagnosis. Miliary pattern on chest radiography is a common finding that has an important role in the early detection of the disease. Nevertheless, approximately 10%-15% of patients have normal chest radiography. Although abnormalities are present, basic hematologic and biochemical tests as well as tuberculin skin test are nonspecific for the diagnosis. Imaging studies are helpful adjunct tools for disseminated TB as they can help determine the involved sites and guide technicians to obtain appropriate specimens for diagnosis. Clinical confirmation of the diagnosis of disseminated TB is usually based on bacteriological or histological evidence. Response to first-line anti-TB drugs is good as evidenced by many reports. This review aims to present a current update on disseminated TB with emphasis on the diagnostic workup of this devastating condition.